2004
DOI: 10.1111/j.1553-2712.2004.tb00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Where's the Beef? The Promise and the Reality of Clinical Documentation

Abstract: Physician-generated emergency department clinical documentation (information obtained from clinician observations and summarized decision processes inclusive of all manner of electronic systems capturing, storing, and presenting clinical documentation) serves four purposes: recording of medical care and communication among providers; payment for hospital and physician; legal defense from medical negligence allegations; and symptom/disease surveillance, public health, and research functions. In the consensus de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Second, documentation has multiple purposes that include, but are not limited to, clinical care. Providers and administrators in our focus groups identified four other key purposes of clinical documentation: administrative, legal, and research -consistent with the goals of the medical record identified in previous research [22][23][24][25][26][27][28][29][30][31] -and medical education, previously unreported and perhaps only applicable to academic training facilities. Nonetheless, the multiple purposes of documentation are consistent with providers' belief that the clinical note is a shared record that serves multiple stakeholders.…”
Section: Discussionsupporting
confidence: 58%
“…Second, documentation has multiple purposes that include, but are not limited to, clinical care. Providers and administrators in our focus groups identified four other key purposes of clinical documentation: administrative, legal, and research -consistent with the goals of the medical record identified in previous research [22][23][24][25][26][27][28][29][30][31] -and medical education, previously unreported and perhaps only applicable to academic training facilities. Nonetheless, the multiple purposes of documentation are consistent with providers' belief that the clinical note is a shared record that serves multiple stakeholders.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, there is still a considerable gap between clinical patient documentation and supplementary data collection for registries, quality assurance and research. This often results in multiple and overlapping documentation activities on various media [ 1 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…On occasion, these statements can be inadvertently included in the medical record. Although EMRs theoretically reduce the cost of documentation via discontinuation of traditional documentation systems (e.g., transcription), their weakness continues to be lost productivity due to the increased time it takes to document an encounter in many, if not most, of the available systems 52,56–59 …”
Section: Ed Information Systemsmentioning
confidence: 99%